The Role of Empathy, Communication, and Emotional Intelligence in Nursing Service Quality at RSIA Bunda Denpasar - Sherlyna Prihandhani, IGAA; Widiastuti, Putu; Bulan Trisna, Made Oktaviani (Babali Publisher, 2024)
Introduction: Nursing services are an integral part of hospital health services, and they have a very strategic position in efforts to improve the quality of consumer services coming to the hospital. The delivery of quality health services highlights the need for multi-stakeholder action at all health system levels. The hospital can maintain patient loyalty and gain public trust by providing efficient and quality services by providing good service. This study examined the effect of empathy, communication, and emotional intelligence on the quality of nursing services at RSIA Bunda Denpasar.Methods: The design of this study was cross-sectional, using a multivariate test and convenience sampling technique. The independent variables in this study were empathy, communication, and emotional intelligence. Meanwhile, the dependent variable in this study is the quality of nursing services at RSIA Bunda Denpasar. The timing of this study is in May 2024. This study used a sampling of 38 respondents. The instruments in this study used empathy, communication, caring, and nursing service quality questionnaires. A validity test value of 0.650-1,000, 0.790-1,000, 0.500-1,000, and 0.545-1,000, and a reliability test value of 0.877, 0.756, 0.765, and 0.867. Results: the results of the multivariate test showed the significance value of each variable has a significance value of <0.005, so the influence of empathy, communication, and emotional intelligence on the quality of nursing services at RSIA Bunda DenpasarConclusion: It is recommended that health service managers improve the quality of human resources by providing nursing services well.